God and George W. Bush : a spiritual life - Kengor, Paul, 1966- (New York : ReganBooks, 2004)
Presents an overview of the spiritual life of United States President George W. Bush, detailing the events that shaped his character and his conversion experience, as well as a discussion of religion in political life.
Preface: Two Hymns and a Purpose -- Robin and Growing Up -- "Mustard Seed" and Compassionate Conservatism -- Texas Raven -- Campaigning for the White House -- "So Help Me God" -- Faith and the Presidency -- "Evildoers" -- Targeting Evil -- When Bush Prays -- God and Democrats -- Saddam -- God and War in Iraq -- War and Freedom in Iraq -- 2004 -- The Mountaintop.
Includes bibliographical references and index.
Keywords: Bush, George W. -- 1946- -- Religion; Church and state -- United States; Religion and state -- United States; Religion and politics -- United States